Terre, normes de propriété et litiges à Kaboul - Antonio De Lauri (Revue des Mondes Musulmans et de la Méditerranée)
Land disputes represent a serious problem in Afghanistan today. Historically, they have several causes. Mass-migration resulting from the war and the influx of returning of refugees has compounded the problems already posed by the lack of effective record-keeping systems and the destruction of official documents. From the starting point of ethnographic case studies, this article develops an analysis of dispute resolution mechanisms related to property. It focuses on normative interconnections, or the way in which different normative systems interact. For instance, in Afghanistan, four normative systems coexist : state law, Islamic law, customary practices and international legal standards. It is argued that judicial practice is the by-product of this normative pluralism and the work of judges is characterized by an ‘art of compromise’ which tends to reify the social hierarchies in place.